Molecular phylogenetics of species of Bulbophyllum sect. Trias (Orchidaceae; Epidendroideae; Malaxidae) based on nrITS and plastid rbcL and matK - Wonnapinij, Passorn; Sriboonlert, Ajaraporn (Phytotaxa, 2015)
Phylogenetic relationships among species of Bulbophyllum sect. Trias and related taxa in Bulbophyllum has not been previously studied due to scarcity of appropriate samples. In this study, we aimed to assess the relationship of these taxa and investigate interspecific relationships of these orchids using DNA sequences from two plastid genes, rbcL and matK, and one nuclear region, nuclear ribosomal internal transcribed spacer, nrITS. Our results showed that all Bulbophyllum sect. Trias species were embedded among other groups of Bulbophyllum, supporting the already published transfer of Trias to synonymy of Bulbophyllum. All trees revealed that the Indochinese sect. Trias form a monophyletic group that could be divided into three groups coincident with their vegetative characters. This study further shows that nrITS sequences can be sufficient for inferring phylogenetic relationship among Trias species, although this marker and the combination of this plus the plastid genes are not able to distinguish the differences between some closely related species.